Mouse Oocytes, A Complex Single Cell Transcriptome - Wu, Di (Frontiers in Cell and Developmental Biology, 2022)
Germinal vesicle (GV) stage is a critical transition point from growth to maturation in mammalian oocyte development. During the following meiotic maturation, active RNA degradation and absence of transcription significantly reprofile the oocyte transcriptome to determine oocyte quality. Oocyte RNA-seq has revealed transcriptome differences between two defined phases of GV stage, namely non-surrounded nucleolus (NSN) and surrounded nucleolus (SN) phases. In addition, oocyte RNA-seq has identified a variety of dysregulated genes upon genetic mutation or environmental perturbation. Historically, due to the low amount of RNA per oocyte, a few (20-200) oocytes were needed for a regular library construction in bulk RNA-seq. In recent years, development of single cell sequencing allows detailing the transcriptome of individual oocytes. Here in this study, different RNA-seq datasets from single and bulk of mouse oocytes are compared, and single oocyte RNA-seq (soRNA-seq) shows higher reproducibility. In addition, soRNA-seq better illustrates developmental progression of GV oocytes, revealing more complex gene changes than traditional views. Specially, an elevated level of ribosomal RNA 5’-ETS (5' external transcribed spacer) has been shown to highly correlate with SN property. This study further demonstrates that UMI (unique molecular identifiers) based and other deduplication methods are limited in their ability to improve the precision of the soRNA-seq datasets. Finally, this study proposes that external spike-in molecules are useful for normalizing samples of different transcriptome sizes. A list of stable genes has been identified during oocyte maturation that are comparable to external spike-in molecules. These findings highlight the advantage of soRNA-seq, and have established ways for better clustering and cross-stage normalization, which can provide more insight into the biological features of oocyte maturation.